2006
DOI: 10.1590/s0100-204x2006001000010
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho e características da carcaça de cordeiros confinados alimentados com grãos de soja

Abstract: Resumo -O objetivo deste trabalho foi avaliar a influência de grãos de soja (GS) no desempenho, características e rendimento de cortes de carcaça de cordeiros confinados. Sessenta e quatro cordeiros Santa Inês, com peso vivo inicial de 19,5±0,19 kg e 75±2 dias de idade, foram distribuídos em blocos ao acaso de acordo com o peso vivo e a idade no início do experimento. Os GS participaram com 0, 7, 14 e 21% na matéria seca (MS) das rações isonitrogenadas experimentais. O consumo de MS (1,1, 1,0, 0,9 e 0,9 kg por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
13
2
27

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 16 publications
14
13
2
27
Order By: Relevance
“…These findings can be considered satisfactory and are explained by the energy concentration of the diet, as well as the genetic potential of the lambs, because all animals had excellent origins. In their study of Santa Inês lambs fed a similar diet, Urano et al (2006) found average to better feed conversion obtained in the present study (3.5).…”
Section: Resultssupporting
confidence: 70%
“…These findings can be considered satisfactory and are explained by the energy concentration of the diet, as well as the genetic potential of the lambs, because all animals had excellent origins. In their study of Santa Inês lambs fed a similar diet, Urano et al (2006) found average to better feed conversion obtained in the present study (3.5).…”
Section: Resultssupporting
confidence: 70%
“…Valores semelhantes também foram obtidos por Urano et al (2006) Rodrigues et al (2008), que encontraram valores médios de 2,0% para para cordeiros da raça Santa Inês mantidos sob o mesmo sistema de produção.…”
Section: Resultsunclassified
“…Urano et al (2006) recommends including soybean at up to 14 kg −1 as dry matter, considering its cost relative to other ingredients.…”
Section: Introductionmentioning
confidence: 99%